The drivers of the great bull stock market of 2015 in China: evidence and policy implications. Issue 2 (2nd April 2020) - Song, Guoxiang
ABSTRACT: This paper investigates what drove the great bull stock market of 2015 in China. Multiple regression models based on the Arbitrage Pricing Theory (APT) theory are developed to describe the variation in stock returns using economic fundamentals. The results indicate that during the normal period, the Chinese stock market was sensitive to economic conditions. However, during the bull market, fundamentals could not justify the variation in the stock returns which are significantly different from the conditional predictions based on the multiple regression model which is robust for the normal period. Margin trading was the main driver of the speculative bubble during the bull market from May 2014 to June 2015. As commercial banks are becoming more exposed to the stock market, the volatility of stock prices may have the potential to increase the risk of the financial system and limit the freedom of China to use monetary policy to deal with economic fundamentals.